Rhizosphere-derived Stutzerimonas stutzeri AUMC B-503: a promising biocontrol and plant growth-promoting strain for managing brown spot disease in rice (Oryza sativa) - Metwally, Sally M.; El-Sapagh, Shimaa; Ali, Sameh S.; Sun, Jianzhong; Schagerl, Michael; Elsherif, Doaa E. (Frontiers in Plant Science, 2025)
Brown spot disease caused by the fungus Bipolaris oryzae severely limits rice production and quality worldwide. The excessive use of chemical fungicides underscores the need for sustainable biological alternatives, such as plant growth-promoting rhizobacteria (PGPR). In this study, four Gram-negative bacterial isolates, designated as P1–P4, were obtained from the rhizosphere of Phragmites australis and evaluated for their plant growth-promoting and antifungal activities. Among these isolates, P3 (molecularly identified as Stutzerimonas stutzeri AUMC B-503) exhibited the highest production of indole-3-acetic acid (IAA) and hydrogen cyanide (HCN), along with strong phosphate-solubilizing capacity and robust biofilm formation. Dual-culture assays revealed that this strain significantly inhibited the mycelial growth of B. oryzae, indicating potent antifungal activity. In agarose-based and pot experiments, AUMC B-503 significantly increased the shoot and root length, biomass, total soluble carbohydrates, and photosynthetic pigment contents of rice seedlings compared with untreated controls. Moreover, inoculated plants exhibited reduced levels of malondialdehyde (MDA) and hydrogen peroxide (H2O2), accompanied by enhanced activities of antioxidant enzymes [polyphenol oxidase (PPO), peroxidase (POD), phenylalanine ammonia-lyase (PAL), and ascorbate peroxidase (APX)] and higher levels of phenolics, flavonoids, ascorbic acid, and total antioxidant capacity. At the transcriptional level, bacterial treatment upregulated the gene expression of OsCHS, OsCHI, and OsFLS, corresponding to the observed increase in total flavonoids. Additionally, the expression of the OsOAT and OsERF83 genes was also elevated, suggesting improved proline metabolism and ethylene/jasmonate-mediated stress signaling. These integrated physiological, biochemical, and molecular responses demonstrate that AUMC B-503 promotes rice growth and enhances tolerance to B. oryzae infection by mobilizing nutrients, activating antioxidants, and inducing the transcription of defense-related pathways. The results highlight AUMC B-503 as a promising and low-risk candidate for promoting rice growth and suppressing brown spot under controlled conditions. The study provides mechanistic evidence for its efficacy while recognizing that biosafety, non-target, and regulatory evaluations are prerequisites for field application.